2003
DOI: 10.1111/j.1346-8138.2003.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Churg‐Strauss Syndrome (CSS) Manifested as Necrosis of Fingers and Toes and Liver Infarction

Abstract: We report a case of Churg-Strauss syndrome (CSS) with necrosis of the fingers and toes and liver infarction. A 59-year-old man with asthma suddenly noticed that his fingers and toes felt unusually cold. This condition worsened progressively, and some digits became necrotic within several weeks. Laboratory studies revealed hypereosinophilia and an extremely elevated serum level of IgE. Digital subtraction angiography of the extremities revealed extensive irregular narrowing of small and medium-sized arteries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Acute hypersensitivity pneumonitis occurs within hours of exposure and should resolve spontaneously within 12-72 hours, which does not fit the clinical picture for our patient. 4 Churg-Strauss angiitis is a necrotizing angiitis that occurs in patients with asthma, 5 neither of which our patient has. Eosinophilic granulomatosis in adults occurs mostly in smokers, 6 and our patient does not smoke.…”
Section: Case Discussion: Fishing For Clues (Dr Suchard)mentioning
confidence: 81%
“…Acute hypersensitivity pneumonitis occurs within hours of exposure and should resolve spontaneously within 12-72 hours, which does not fit the clinical picture for our patient. 4 Churg-Strauss angiitis is a necrotizing angiitis that occurs in patients with asthma, 5 neither of which our patient has. Eosinophilic granulomatosis in adults occurs mostly in smokers, 6 and our patient does not smoke.…”
Section: Case Discussion: Fishing For Clues (Dr Suchard)mentioning
confidence: 81%
“…However, this was not likely in the present patient, because the inflammation around the hepatic artery was demonstrated by the liver biopsy and the expression of MRP2 was normal. Digital subtraction angiography revealed irregular narrowing of the small arteries in the liver in a patient with Churg–Strauss syndrome 4 . A recent study demonstrated eosinophilic infiltrates in vessels in the portal area of the liver in a patient with Churg–Strauss syndrome 5 .…”
Section: Discussionmentioning
confidence: 91%
“…The symptoms are palpable cutaneous purpura, mononeuritis multiplex, gastrointestinal involvement and renal involvement. Liver involvement is rare, however, some studies described liver function abnormalities 4,5,7 . Severe systemic inflammation affects liver function, especially various transporters and tight junction proteins of hepatocytes 8–10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare cases of intestinal erosion,4 ulceration and perforation3 7 8 have been described. Others include acalculous cholecystitis associated with large liver abscesses,4 liver infarction with cutaneous necrosis,5 and duodenitis 6. One case of oophoritis, complicating interpretation of the abdominal signs in women, has also been documented 9…”
Section: Discussionmentioning
confidence: 99%